Nutritional Status of Children under Five Years in the Working Area of Puskesmas Manutapen - Cindy F. Hawu; Marselinus Laga; Enjelita Ndoen (Universitas Nusa Cendana, 2022)
Nutritional problems in children under five, such as undernutrition can affect their health. The purpose of the study was to analyze the factors related to the nutritional status of children under five of age in the working area of the Manutapen Public Health Center in 2021. This was a quantitative study using a Cross-Sectional design involving 90 mothers of toddlers and children under five with the cluster random sampling technique. The results showed that the factors related to the nutritional status of children under five were the mother's education level (p=0.030), family income level (p=0.014), mother's level of knowledge (p=0.001), history of infectious disease (p=0.026), and the number of family members (p=0.005). The Manutapen Public Health Center is expected to maximize regular counseling activities about toddler nutrition and the use of health promotion media. Moreover, an active role from Nutrition Implementation Personnel and Health Promotion Programs is necessary to increase counseling efforts about the importance of nutritious food for toddlers.